The Judgement of the Mummy - Christian Jacq (London, United Kingdom Simon & Schuster Ltd, 2009)
London,1821. Recently returned from Egypt, the adventurer Giovanni Belzoni enthrals Londoners with the city's first exhibition devoted to Egyptian art. As he unveils his star exhibit, a mummy so perfectly preserved it seems almost alive, there is a collective intake of breath. The astonishing spectacle provokes an immediate scandal: a hysterical preacher demands the destruction of this pagan relic; an elderly Lord wants to feed it to his dogs; a pathologist wishes to keep the body in order to study this fascinating phenomenon. But the following night the mummy disappears - and the preacher, the Lord and the pathologist are murdered. For the country's foremost detective, Inspector Higgins, the prime suspect is none other than the mummy itself. He is also convinced that the mummy's disappearance is closely linked to the revolutionary conspiracy causing unrest in London's most squalid districts. Assisted by the beautiful Lady Suzanna, will Inspector Higgins succeed in solving the puzzle before the mummy's inescapable judgement?
Keywords: Detective / Crime -- Detective / Crime